Comparison of ELISA and DNA Lateral Flow Assays for Detection of Pork, Horse, Beef, Chicken, Turkey, and Goat Contamination in Meat Products. (23rd November 2019) - Ha, Youngsil; Thienes, Cortlandt P; Agapov, Alexander A; Laznicka, Amanda V; Han, Sukkyun; Nadala, Cesar; Samadpour, Mansour
Abstract: Background: Concerns about the contamination of meat products with undeclared meats and new regulations for the declaration of meat adulterants have established the need for a sensitive test to detect meat adulteration. To address this need, Microbiologique, Inc. has developed ELISA assays that can detect the presence of pork, horse, beef, chicken, turkey, and goat meat adulterants to 0.1% (w/w) and a deoxyribonucleic acid (DNA) lateral flow assay for pork, horse, beef, chicken, turkey, goat, and lamb adulterants to 0.1% (w/w). Objective: We compared the results of the DNA lateral flow assay to the ELISA assays. Methods: ELISA and DNA lateral flow assays were performed on the same spiked meat samples, prepared meats, and pet foods. Results: Both the DNA lateral flow and the ELISA assays were sensitive to 0.1% meat adulterant, and the agreement between the DNA lateral flow and ELISA assays for spiked samples, prepared meat, and pet foods was 100%. Conclusions: Based on the 100% concordance between the two assay formats, the choice between the two is dependent on whether quantitation is desired, which assay is more familiar to the particular laboratory, availability of the required equipment, and time restrictions. Highlights: The ELISA assays are less time consuming, taking about 1.5 h, compared with about 2.5 h for the DNA lateral flow assay. Because the DNA lateral flow test detects seven species in one test, it can be more cost effective when the potential adulterant is not known, while the ELISA may be better for quantification.